The Influence of Workload, Work Fatigue, and Work Behavior on Work Accidents for Female Workers in Informal Sectors in Kupang City - Berek, Noorce Christiani; Ruliati, Luh Putu; Ndun, Helga J. N; Nabuasa, Diana Juniati (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2022)
A workplace accident is an unwanted and often unforeseen event that can result in lost time from work, property damage, or death. Work accidents, work fatigue, and worker behavior are some of the problems that are often faced by informal sector workers. The goal of this research was to look into the factors that impact work accidents among women in Kupang's informal sector. An observational study with a cross-sectional design was used in this investigation.From April to July 2019, this research was conducted in Kupang City. Participants in this study were 548 women who worked in the informal sector. The research sample consisted of 140 women from the informal sector who were selected using a basic random selection approach. Interviews were used to obtain data, which was then analyzed bivariately using a basic linear regression test. Workload was discovered to be a factor in the study's findings (0.000) and work fatigue (0.000) affected work accidents, while work behavior (0.076) did not affect work accidents in female workers. Occupational Health and Safety (OHS) procedures and rules in the workplace, counseling regarding the application of OHS with workers, as well as sanctions against the application of OHS in the workplace to workers need to be implemented to reduce workplace accidents.